Preparation of Nanoscale Iron (Oxide, Oxyhydroxides and Zero-Valent) Particles Derived from Blueberries: Reactivity, Characterization and Removal Mechanism of Arsenate - Rubio-Campos, M; Arancibia-Miranda, N; Arancibia-Miranda, N; Manquian-Cerda, K; Manquian-Cerda, K (Academic Press, 2017)
The application of iron nanoparticles (FeNPs) to the removal of various pollutants has received wide attention over the last few decades. A synthesis alternative to obtain these nanoparticles without using harmful chemical reagents, such as NaBH4, is the use of extracts from different natural sources that allow a lesser degree of agglomeration, in a process known as green synthesis. In this study, FeNPs were synthesized by ‘green’ (hereafter, BB-Fe NPs) and ‘chemical’ (hereafter, nZVI) methods. Extracts of leaves and blueberry shoots (Vaccinium corymbosum) were used as reducing agents for FeCl3·6H2O solution in the green synthesis method. FeNPs were characterized using transmission electron microscopy (TEM), scanning electron microscopy (SEM), electrophoretic migration, Brunauer-Emmett-Teller (BET) surface area analysis and X-ray diffraction (XRD) and evaluated for the removal of As(V) from aqueous systems. In both synthesis methods, XRD analysis confirmed the presence of the different kinds of iron nanoparticles. SEM analysis showed that the average size of BB-Fe NPs was 52.4 nm and that a variety of nanoparticles of different forms and associated structures, such as lepidocrocite, magnetite, and nZVI, were present, while the dimensions of nZVI were 80.2 nm. Comparatively significant differences regarding the electrophoretic mobility were found between both materials pre- and post-sorption of As(V). The velocity of As(V) removal by BB-Fe NPs was slower than that by nZVI, reaching equilibrium at 120 min compared to 60 min for nZVI. The removal kinetics of As(V) were adequately described by the pseudo-second-order kinetic model, and the maximum adsorbed amounts of this analyte are in close accordance with the experimental results. The Langmuir-Freundlich model is in good agreement with our experimental data, where the sorption capacity of nZVI and BB-Fe NPs was found to be 52.23 ± 6.06 and 50.40 ± 5.90 (mg·g−1), respectively. The use of leaves of Vaccinium corymbosum affords an easy-to-synthesize, low-cost, and eco-friendly material with capabilities similar to nZVI. BB-Fe NPs are promising for arsenic remediation, which has emerged as a new alternative for water purification and sanitation. © 2017 Elsevier Inc.